Current approaches for the discovery of drugs that deter substance and drug abuse - Yasgar, Adam (Expert Opin Drug Discov, 2014)
INTRODUCTION: Much has been presented and debated on the topic of drug abuse and its multidimensional nature, including the role of society and its customs and laws, economical factors, and the magnitude and nature of the burden. Given the complex nature of the receptors and pathways implicated in regulation of the cognitive and behavioral processes associated with addiction, a large number of molecular targets have been interrogated during recent years to discover starting points for development of small molecule interventions. AREAS COVERED: This review describes recent developments in the field of early drug discovery for drug abuse interventions, with a special emphasis on advances published during the 2012-2014 period. EXPERT OPINION: Technologically, the processes/platforms utilized in drug abuse drug discovery are nearly identical to those used in the other disease areas. A key complicating factor in drug abuse research is the enormous biological complexity surrounding the brain processes involved and the associated difficulty in finding “good” targets and achieving exquisite selectivity of treatment agents. While tremendous progress has been made during recent years to use the power of high-throughput technologies to discover proof-of-principle molecules for many new targets, next-generation models will be especially important in this field; examples include seeking advantageous drug-drug combinations, use of automated whole-animal behavioral screening systems, advancing our understanding of the role of epigenetics in drug addiction, and the employment of organoid-level 3D test platforms (also referred to as tissue-chip or organs-on-chip).